My Class : From Russia with Relativity - Eremenko, Ekaterina (Germany : Zero One Film, 2008)
“My Class” is a film about the brain drain, about tradition and globalization, about materialism and anti -idealism and not least about national identity. In 1982, 26 young specially gifted pupils were accepted to the school for Natural Sciences in the Soviet Union. Graduating from this school guaranteed a promising future. After Perestroika and the fall of the Soviet Union, these special students disappeared. The director, one of the students herself, goes on a personal journey into her past in order to meet her former classmates and to find out what has become of them.
With voice-over in English
Verzio Film Festival Submission